Information System Location Selling Coffee Using Google Maps - Hsb, Mhd Diansyari; Syahputra, Edy Rahman (Al'Adzkiya, 2023)
The existence of suppliers in the coffee industry is very important in maintaining business continuity. Coffee farmers in general are still faced with a coffee trade system that is still controlled by traders. This trading system condition can regulate coffee sales transactions, both with regard to time, place and to whom the farmers' coffee beans are sold. The purpose of this research is to make it easier for sellers and buyers of coffee to find the whereabouts of coffee sellers. This research uses the Google Maps API to decide the location of coffee sales. In addition, this application is built using supporting software Android Studio and MySQL database. The results of the research show that the application functions properly without any errors or debug when the testing program is carried out where the results of the processing system display, including being able to find the location of the farmer, knowing the number of available coffee stocks and showing the way to the farmer's site. Keyword : Coffee Farmers, Sales Locations, Google Maps, Android